Establishment of methodology for drying leaves and storage of essential oil of linalool chemotype Ocimum basilicum L. (Bioscience Journal, 2015)
The aim of this study was to evaluate the influence of leaf drying and oil storage on the content and chemical composition of the essential oil of linalool type basil (Ocimum basilicum L.) cultivar Maria Bonita. In the first trial, the effect of the drying time of leaves a temperature of 40°C. In the second trial, the effect of storage time evaluated (0, 15, 30, 60, 90, 120, 150, 210, 240 and 270 days) at two temperatures [room (Â±27°C) and freezer (-20°C Â± 2°C) temperature]. The essential oil was extracted by hydrodistillation of leaves and analyzed by GC and GC/MS. The drying process was efficient, reducing the moisture content 84.5% to 1.3% over a period of eight days. There was a linear reduction in the essential oil (6.0% to 3.9%), of linalool (6.38% to 74.09%), increase of the content of Î±-trans-bergamotene (1.1% to 1.8%) and epi-Î±-cadinol ( 1.57% to 1.77%). In the second trial, we noted increase of the linalool content from 76.99% to 79.40% after 210 days of storage at room temperature and to 79.82% after 240 days of storage in freezer. We can conclude that basil essential oil can be stored for up to seven months at room temperature and eight months in freezer.